Descriptive analysis of the conservation conditions of a foraging site for the Pacific green turtle (Chelonia mydas agassizii, Testudines: Chelonioidea) in Golfo Dulce, Costa Rica, based on the turtle’s state of health and the discovery of pesticides in the environment - Sarmento, Martha (2016)
The development of management strategies for the conservation of Golfo Dulce and of sea turtles requires inputs related to the current health status of the populations of the turtles. Several studies have linked the clinical manifestation of diseases such as fibropapillomatosis (FP) in sea turtles with environmental stressors and anthropogenic activities, which may result in the presence of contaminants and environmental degradation of foraging and nesting areas. This paper was prepared considering this link and as an environmental characterization of a foraging site based on the state of health of the Pacific green turtle (Chelonia mydas agassizii) and the environmental conditions of this site (a foraging site) in Golfo Dulce, Costa Rica, between 2010 and 2012. To this end, the physical condition of 77 turtles, the presence of fibropapillomatosis (FP) and the molecular detection of CFPHV were determined. An analysis was performed considering the following factors: land use and population density near the study area, as well as the presence of pesticides in samples of marine sediment, water and seagrass, and blood from 10 turtles. One of the results indicates that the general condition of the gulf is preserved, solely with the presence of rice crops near the area and a sector with a significantly growing population. The study determined the presence of the herbicide clomazone as well as the good health of the turtles studied, apparently free from FP. However, the possible FP casual agent was molecularly detected in 26% (20) of the sampled individuals. With this research, Golfo Dulce was recognized as an important foraging site with adequate conditions for the preservation and protection of the Pacific Green Sea Turtle.